Altering the Biodegradation of Mesoporous Silica Nanoparticles by Means of Experimental Parameters and Surface Functionalization. (7th March 2018) - Seré, Stephanie; De Roo, Bert; Vervaele, Mattias; Van Gool, Stefaan; Jacobs, Sandra; Seo, Jin Won; Locquet, Jean-Pierre
Abstract : Mesoporous silica nanoparticles (MSNPs) are gaining a large interest in the field of medical and biomedical applications due to their biodegradability and high loading capacity as a carrier. In this work, a simple synthesis and functionalization procedure is reported, which allows tuning the nanoparticle properties, functionalization, and biodegradability. Variations in the synthesis procedure are introduced, including temperature, concentration of catalyst, and surface functionalization. These samples are characterized and afterwards degraded in phosphate buffered saline (PBS) to determine their degradation kinetics. The amount of degraded material is colorimetrically determined, using an optimized protocol based on molybdenum blue chemistry. It is shown that the degradability of the nanoparticles increased with decreasing synthesis temperatures, lower amounts of catalyst, and higher concentrations of nanoparticles. Surface functionalization alters the degradation kinetics as well, rendering amino-functionalized nanoparticles the fastest degradation behavior, followed by carboxylated and nonfunctionalized nanoparticles. From these results, it can be concluded that the degradation rate of MSNPs can be varied from a few hours to several days by small changes in the synthesis procedure. Moreover, the degradation behavior is strongly dependent on the nanoparticle growth rate.